IMPLEMENTASI SISTEM INFORMASI MANAJEMEN NIKAH GANDA: STUDI KEBIJAKAN STRATEGIS TRANSFORMATIF DAN EFEKTIVITAS HUKUM - Sakinah, Neila; Masdar Hilmy, Ahmad Arif (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2019)
The web-based Marriage Management Information System (SIMKAH) is a new system that is used in the Office of Religious Affairs (KUA) Districts throughout Indonesia, replacing the desktop-based SIMKAH. Although Regulation No. 20 of 2019 regarding Marriage Registration has been passed to fully switch to web-based SIMKAH, the KUA of Gayungan, Surabaya, instead chose to implement Dual SIMKAH, which is web and desktop based. This article aims to find out the description and implementation of Dual SIMKAH in KUA of Gayungan, as well as a review of transformative strategic policies and legal effectiveness on the implementation of the Dual SIMKAH. This field research uses descriptive qualitative methods. Data mining is done through in-depth observation and interviews, as well as hands-on experience so that goals can be realized. This study produces several conclusions: (1) the implementation of Dual SIMKAH is very much needed as an anticipative effort when web-based SIMKAH experiences problems, especially in server repair, (2) the implementation of Dual SIMKAH can be assessed as a transformative strategic policy, (3) at the technical level, implementation Web-based SIMKAH still contains various problems, such as the application of Dual SIMKAH which has more support, old habits that are still inherent, the absence of announcements when the server will be repaired, and social conditions that make it impossible to switch completely to web-based SIMKAH.